Multifaceted roles of FD gene family in flowering, plant architecture, and adaptation - Yang, Hui; Zhong, Meiling; Liu, Yucheng; Chen, Liyu; Liu, Baohui; Kong, Fanjiang; Li, Hong; Yue, Lin (Frontiers in Plant Science, 2025)
FD gene family encodes transcription factors with a basic region/leucine zipper (bZIP) domain that play an essential role in floral transition regulation, which is vital for plants’ reproduction. Recent studies have uncovered additional functions for FD gene family in plant development, hormone signaling, and response to environmental cues. These pleiotropic roles make them promising targets for modern crops’ breeding. Here, we systematically review the diverse functions and regulation mechanisms of FD gene family in model plants and several crops, to provide important insights into their roles. By summarizing the current understanding of their molecular mechanisms, we aim to highlight their potential as key targets for improving crop yield, stress tolerance, and adaptation to changing climates. Furthermore, we propose future research directions, these efforts will pave the way for the effective utilization of them in modern crop breeding programs.